Anterior knee pain and patellar instability - Sanchis-Alfonso, Vicente (Springer, 2011)
As this work is published, at the beginning of the 21st Century, a new perspective of the classic orthopedic enigma of the patellofemoral pain problem is becoming increasingly accepted. It is clear that the decades-old paradigm of a pure structural and biomechanical explanation for the genesis of patellofemoral pain is inadequate, and that a new era has begun with biological factors now being given more consideration. This book is organized into sections which have been reformatted from the first edition. Unlike other publications, this work gives great importance to the etiopathogeny; the latest theories are presented regarding the pathogeny of anterior knee pain and patellar instability, although in an eminently clinical and practical manner. With contributions from orthopedic surgeons, physiotherapists, radiologists, biologists, pathologists, bioengineers, and plastic surgeons this multidisciplinary book will serve as an authoritative reference on one of the most problematic entities currently in the pathology of the knee.